Relationship between climate variability and mass removal processes. Tunja-Páez case study - July Katerine Rojas-Mesa; Luis Carlos Leguizamón-Barreto; Luis Alfredo Vega-Báez (Dyna)
This article focused on the relationship between the influence of climatic variables and seismic activity in the dynamics of slopes that presented mass removal phenomena in the case study: Tunja-Páez Corridor. This analysis was carried out through the application of a probabilistic model that integrated parameters of soil resistance, seismic activity, and accumulated precipitation to establish the definition of rainfall thresholds obtained from the rainfall records preceding each of the removal events. This model used first order, second moment FOSM, and the Poisson distribution of probabilistic foundations to estimate the probability of failure of given slope. Additionally, the change in precipitation in the years 2040, 2070, and 2100 as defined by forecasts of Climate Change (CC) according to IDEAM were used to compare the effects on the probability of soil saturation.